Penguatan Literasi Manajemen Publikasi Jurnal Ilmiah Berbasis Akreditasi Jurnal Nasional (Arjuna) - Mathar, Taufiq; Astrid, Andi Fauziah; Haruddin; Irawati (Faculty of Tarbiyah and Teacher Training, 2026)
This mentoring program aimed to enhance the capacity of scientific journal managers at Universitas Al Asyariyah Mandar, STIBA Makassar, STAI Al Azhar Gowa, and Universitas Islam Ahmad Dahlan (UIAD) Sinjai, particularly in understanding and implementing the National Journal Accreditation guidelines (ARJUNA). The mentoring was conducted through a phased approach that included mapping the initial conditions of the journals, reviewing editorial governance, analyzing article content, as well as engaging in discussions and hands-on practice in journal management using the Open Journal Systems (OJS) platform. The identification results indicate that the assisted journals generally face similar challenges, including weak documentation of editorial policies and publication ethics, suboptimal peer-review mechanisms, limited diversity among editorial boards and reviewers, low article readability quality, and inconsistent publication schedules. The mentoring subsequently focused on strengthening ARJUNA literacy by outlining journal quality improvement strategies based on best practices derived from journals accredited at SINTA 2. These strategies encompassed the structuring of transparent and standards-compliant journal policies, strengthening the roles of editors and reviewers, implementing systematic and well-documented editorial workflows, improving article quality through more rigorous manuscript selection, and enhancing metadata quality and journal presentation. The implications of this activity demonstrate that the mentoring process not only contributes to improvements in the technical and administrative aspects of journal management but also fosters a paradigm shift toward more strategic, sustainable, and academically quality-oriented journal governance. Accordingly, mentoring serves as an important institutional learning process in preparing these journals to advance their accreditation status toward SINTA 2.